2017
DOI: 10.1001/jamaophthalmol.2016.4597
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Psychometric Properties of a Questionnaire Assessing Patient-Reported Outcomes With Laser In Situ Keratomileusis (PROWL)

Abstract: IMPORTANCE Patient-reported outcome (PRO) measures for laser in situ keratomileusis (LASIK) are needed.OBJECTIVE To develop PRO measures to assess satisfaction, eye-related symptoms, and their effect on functioning and well-being following LASIK based on patient and expert input. DESIGN, SETTING, AND PARTICIPANTSThe Patient-Reported Outcomes With LASIK (PROWL) studies were prospective observational studies of patients undergoing LASIK surgery for myopia, hyperopia, or astigmatism. PROWL-1 was a single-center s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…As postoperative UDVA is related to the QOL, the improvement in QOL would result in higher satisfaction with LASIK surgery. 6 9 When considered together, we speculate that LASIK surgery could contribute to patients’ subjective happiness by improving the QOL.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As postoperative UDVA is related to the QOL, the improvement in QOL would result in higher satisfaction with LASIK surgery. 6 9 When considered together, we speculate that LASIK surgery could contribute to patients’ subjective happiness by improving the QOL.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported improvements in the QOL of patients after LASIK. 6 9 Lazon de la Jara et al reported improvement in the QOL of myopia patients after LASIK using the Institute for Eye Research multidimensional QOL scale for myopia. 7 Their research confirmed that LASIK improved the patients’ adaptability, confidence, and sense of well-being, allowing them to have a more optimistic attitude about their lives and increased perceived QOL after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In each of the PROWL studies, less than 1% of patients experienced difficulty performing their usual activities following LASIK surgery due to any one symptom and more than 95% were satisfied with their vision. [59][60][61][62][63] As so few patients experienced debilitating symptoms, the FDA decided with its limited resources not to conduct a larger clinical study to estimate prevalence of complications more accurately or find useful predictors in post-LASIK patients.…”
Section: Outcomes and Patient Satisfaction After Lvcmentioning
confidence: 99%
“…Chronic ocular surface pain has also been associated with refractive surgery [ 43 ]. Dry eye symptoms are common in the first month post photorefractive keratectomy (PRK) [ 41 ] or laser in-situ keratomileusis (LASIK), typically with resolution over the following months, according to the Patient Reported Outcomes With LASIK (PROWL) study [ 44 ]. In the PROWL-1 study, the mean OSDI of 215 patients was significantly less at the six-month post-op period compared to pre-procedure baseline (8 vs. 14, p < 0.001) [ 44 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Dry eye symptoms are common in the first month post photorefractive keratectomy (PRK) [ 41 ] or laser in-situ keratomileusis (LASIK), typically with resolution over the following months, according to the Patient Reported Outcomes With LASIK (PROWL) study [ 44 ]. In the PROWL-1 study, the mean OSDI of 215 patients was significantly less at the six-month post-op period compared to pre-procedure baseline (8 vs. 14, p < 0.001) [ 44 ]. However, rare cases have been documented of persistent refractory ocular surface pain, light sensitivity, and visual difficulty after surgery, often in the absence of ocular surface signs or other triggers [ 45 , 46 ].…”
Section: Epidemiologymentioning
confidence: 99%